ANALISIS PENDAPATAN USAHA GULA AREN DI DUSUN KALATIN, KECAMATAN RATAHAN KABUPATEN MINAHASA TENGGARA - Erffelient ., Porobaten; O. Esry H. Laoh; Nordy F. L. Waney (AGRI-SOSIOEKONOMI, 2017)
This study aims to see how much income earned by farmers. This study was conducted from July to September 2017. The data used are primary data and secondary data. This research was conducted by direct interview technique with 18 (eighteen) respondents in this case palm sugar processor and also using written data in document form obtained from village head of North Lowu Village. The data obtained will be analyzed using descriptive analysis and will be presented in tabular form. Total acceptance of all palm sugar processors in Kalatin Hamlet, amounting to Rp.3.310.000 / day of the total revenue obtained by all palm sugar processing with a cost incurred of Rp.2.411.902 then, obtained profit by 18 processors that is Rp.898.098 / day if not calculated raw material costs, then each processor gain profit Rp.49.898/day. However, if calculated raw material costs then the losses experienced by all palm sugar processing that is Rp.-2.903.902 / day with the cost incurred is Rp. 6.213.902 and each processor suffered loss of Rp.- 161.327 / day. If the cost for the raw material and labor were not included, the processing of palm sugar in Kalatin Hamlet is economically and feasible to be cultivated by R / C = 1,37.